A imagem do etanol como desenvolvimento sustentável e a (nova) morfologia do trabalho - de Moraes Silva, Maria Aparecida [UNESP]; de Verçoza, Lúcio Vasconcellos; Bueno, Juliana Dourado (FapUNIFESP (SciELO), 2013)
The aim of this text is to analyze labor relations and conditions in sugar cane fields which have resulted from the labor reconfiguration process as related to the current situation of intensified mechanization of the sugar cane harvest. Due to the rapid changes which have occurred in the harvest, we feel that these labor relations must be analyzed within the context of the sustainable development image projected by sugar and ethanol companies and by the Brazilian government. Intensification of the exploitation of the work force in the setting of a (new) morphology combines highly advanced technology with increasing under-qualification of the labor force. These reflections will aim to bring to the surface the social reality hidden behind the ideology fabricated to sustain this economic activity. We seek a critical analysis of the developmentalist ideology inherent to this type of production. The methodology employed is based on oral history and direct observation in the sugar cane fields of the states of São Paulo and Alagoas.
The image of ethanol as sustainable development and the (new) morphology of labor
Keywords: Capitalism in the fields; Labor relations; Sugar cane; Working conditions